Haunting Vocabulary and Celtic Lexicography: Towards a Taxonomy of Ghost Words - Harvey, Anthony (Studia Celtica Posnaniensia, 2019)
Most Humanities scholars probably have an intuitive sense of what is meant by a “ghost word” – it is a word that, in one way or another, exists as the result of someone’s unrecognized mistake. However, upon closer examination it becomes clear that the term is liable to be employed so broadly that important distinctions can be lost. For one thing, ghost words are often regarded simply as nuisances that should be deleted whenever they are detected. But in practice they often prove to be too useful simply to discard: this article presents some examples that have made their way into active usage among the Celts. In other cases the etymology may indeed be unnatural, but turns out to be the result of more than a hint of deliberate word-crafting right from the start. A taxonomy is here proposed that distinguishes true ghost words and dead words, on the one hand, from active items that may be described as poltergeist words and even Frankenstein words on the other.